PENOLAKAN MASYRAKAT KAMPUNG LUWUK DAN LENGKO LOLOK TERHADAP RENCANA PEMBANGUNAN TAMBANG BATU GAMPING TAHUN 2020 (Jurnal Nawala Politika, 2023)
ABSTRACT This research aims to explain the refusal made by the residents of Luwuk and Lengko Lolok Village towards the presence of limestone mine in 2020, rejection from local residents causes conflicts between fellow communities as well as the government. This study uses conflict theory using descriptive qualitative research methods to describe the reasons for the rejection and the actions and conflicts that occur. The result of this study found that: (1) management space for local residents field and gardes also disturbs their cultural order because this limestone mine devolpment plan requires local residents to relocate, (2) conflicts that accur are caused by differences in the apspirations of local residents who reject and accepted the presence of this challenge. The construction of this limestone could have been carried out of it did not relocate the village which caused local residents to lose their identiy as Luwuk and Lengko Lolok People. Keyword: Conflict, NTT mining, Perception